PENGGUNAAN MULTIMEDIA INTERAKTIF TERHADAP MEMBACA PERMULAAN PADA ANAK KESULITAN BELAJAR DI KELAS RENDAH - TAMA KURNIAWAN, EDY (Jurnal Pendidikan Khusus, 2016)
Abstract   Beginning reading ability was one of the basic aspects in reading which had to be mastered by every child. Beginning reading ability to the difficulty learning children could be developed using interactive multimedia. An interactive multimedia was learning media which could stimulate the user to be active through the sense organs by involving optimally the children’s ability about the material in reading. The purpose of this research was to prove the influence of interactive multimedia toward beginning reading to difficulty learning children in SDN Banjaranyar II Kras Kediri. The subject of this research was difficulty learning children of class I numbering 6 children. This research used quantitative method with pre-experiment design arrangement and one group pre-test post-test design kind. The data was collected by test technique. The technique of data analysis used statistic non parametric with wilcoxon match pair test. The research result indicated that there was influence of interactive multimedia toward beginning reading to difficulty learning children in low class. It was seen from the research result which indicated that zh = 2,20 > zt = 1,96 which meant that “there was significant influence of interactive multimedia toward beginning reading to difficulty learning children in low class”.    Keywords: Beginning reading, interactive multimedia